2014
DOI: 10.1093/schbul/sbu097
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity of the Nucleus Accumbens in Auditory and Visual Hallucinations in Schizophrenia

Abstract: Both auditory hallucinations (AH) and visual hallucinations may occur in schizophrenia. One of the main hypotheses underlying their occurrence involves the increased activity of the mesolimbic pathway, which links the ventral tegmental area (VTA) and the nucleus accumbens (NAcc). However, the precise contribution of the mesolimbic pathway in hallucinations across various sensory modalities has not yet been explored. We compared the resting-state functional connectivity (rs-FC) of the NAcc among 16 schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 50 publications
5
67
0
1
Order By: Relevance
“…12 Rolland et al 12 found that mesolimbic connectivity patterns changed with escalating sensory complexity of the experiences (eg, 0, 1, or 2 modalities). Relative to patients that did not endorse hallucinations in any sensory domain and those that endorsed hallucinations solely in the auditory domain, Sz patients that endorsed both VH and AH had significantly elevated parahippocampal, insular and striatal connectivity with the nucleus accumbens, while significant differences in hippocampal connectivity were not found between the pure AH group and NH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Rolland et al 12 found that mesolimbic connectivity patterns changed with escalating sensory complexity of the experiences (eg, 0, 1, or 2 modalities). Relative to patients that did not endorse hallucinations in any sensory domain and those that endorsed hallucinations solely in the auditory domain, Sz patients that endorsed both VH and AH had significantly elevated parahippocampal, insular and striatal connectivity with the nucleus accumbens, while significant differences in hippocampal connectivity were not found between the pure AH group and NH.…”
Section: Discussionmentioning
confidence: 99%
“…Due to AH prevalence in Sz, these studies are designed to assess FC differences across patient groups that endorse both VH and AH vs patients that endorse only AH. Relative to patients that endorsed only AH, patients that endorse VH and AH show functional hyperconnectivity with subcortical structures including caudate, 11 putamen, 12 amygdala, 13 nucleus accumbens, 12 parahippocampus, 12 and hippocampus. 11,13 We posit that Sz patients that endorse AH will have distinct, dynamic patterns of rs-activity in comparison to patients that endorse both VH and AH.…”
Section: Introductionmentioning
confidence: 90%
“…En effet, le signal codant pour une erreur de pré diction dans une structure dopaminergique sous-corticale, le striatum, augmente le couplage de structures corticales distantes [11], et pourrait ainsi renforcer leur association sous-tendant l'idé e dé lirante. De maniè re inté -ressante et en parfaite continuité avec ces hypothè ses, des anomalies de connectivité fonctionnelle du striatum ventral ont ré cemment pu être mises en é vidence dans la schizophré nie, recrutant des ré seaux neuronaux variables en fonction de la complexité hallucinatoire des sujets [37].…”
Section: Simuler La Transition Psychotiqueunclassified
“…In their recent publication, Rolland and colleagues (Rolland et al, 2014) linked hallucinations in patients with schizophrenia to connectivity between the nucleus accumbens (NAc), ventral tegmental area (VTA), and a number of other regions generally consistent with what we referred to as the brain reward circuit. Moreover, they noted in their letter that the circuitry that we found to be affected by THC and smoked cannabis has also been implicated in psychosis in schizophrenia, and that cannabis smoking can increase positive symptoms in these patients.…”
Section: To the Editormentioning
confidence: 99%